Analisis Pengaruh Arus Kas Operasi Terhadap Penjualan Pada PT. Borwita Citra Prima Cabang Bima - Aswin Waraihan; Nurhayati Nurhayati (Media Ekonomi, 2021)
This study aims to determine the effect of operating cash flow on sales at PT. Borwita Citra Prima Branch of Bima from 2015 to 2019. The type of data used is internal primary data in the form of financial report data at PT. Borwita Citra Prima. The sampling technique used purposive sampling for 5 years from 2015 to 2019. The data analysis technique used was simple linear regression, correlation coefficient, coefficient of determination and hypothesis testing (2-party t test ). The results of this study indicate that operating cash flow has no significant effect on sales, because the t value is smaller than the table t table (1.494 <3.182) with a significant value of 0.232 at PT. Borwita Citra Prima, Bima Branch. The magnitude of the effect of operating cash flow on sales is 42.7% and 57.3% is a component outside of research.